A Cognitive Grammatical Study of Possessive Constructions in Orwell’s ‘A Clergyman’s Daughter’ - Hammad, Alaa Nawzad Aula; Lutfi, Abbas Fadhil (European Scientific Journal, ESJ, 2019)
This paper focuses on investigating the syntax and semantics of possessive constructions in A Clergyman’s Daughter at the phrasal level, within the framework of cognitive grammar using Heine’s (1997) model of possessives. The study aims at analyzing the various semantic relations in possessive constructions from a cognitive grammar perspective, and showing that possession does have a privileged status in the semantics of other concepts. This, however, proves the fallacy of the traditional view. It also shows that there is a natural and systematic relationship between possessive constructions and cognitive constructional schemas that give rise to them through conceptual transfer, and are motivated by experiential gestalt. No model alone can account for all semantic relations expressed through prototypical possessive. After analyzing possessive structures using Heine’s (1997) classification of possessives, there remains a group of other semantic relations that Heine (1997) could not have given a label; they are uncategorized. For underlying grammatical structures of these possessives, Lakoff and Johnson’s (1980) model is used, which propose that aspects of the experiential gestalt motivate the wider use of too complex possessive constructions.